2017
DOI: 10.3892/ol.2017.7512
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which CXCR4/CXCL12 cause metastatic behavior in pancreatic cancer

Abstract: Abstract. C-X-C motif chemokine receptor (CXCR) 4/CXCL12 is associated with tumor invasion and metastasis in pancreatic cancer. The present study aimed to investigate the possible mechanisms behind this process by studying the association between the expression of CXCR4 and numerous molecular markers. A total of 60 patients with pancreatic cancer who had been treated with radical surgery between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…This chemokine and its corresponding receptor (CXCR4) are believed to play a crucial role in many solid cancers, and are associated with metastatic spread in breast cancer, lung cancer and melanoma [40][41][42][43]. Accumulating evidence also points to a role in PDAC progression, with higher expression of CXCL12 correlating with metastasis, likely by facilitating immune evasion, and increased levels of matrix metalloproteinases leading to cellular invasion [44][45][46][47]. Within our own study, we find similar trends in the presence of other cellular populations that parallel the emergence of CXCL12-expressing iCAFs, such as a decrease in cytotoxic T cell and increase in myeloid suppressive proportions, creating the notorious immune suppressive TME well described in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…This chemokine and its corresponding receptor (CXCR4) are believed to play a crucial role in many solid cancers, and are associated with metastatic spread in breast cancer, lung cancer and melanoma [40][41][42][43]. Accumulating evidence also points to a role in PDAC progression, with higher expression of CXCL12 correlating with metastasis, likely by facilitating immune evasion, and increased levels of matrix metalloproteinases leading to cellular invasion [44][45][46][47]. Within our own study, we find similar trends in the presence of other cellular populations that parallel the emergence of CXCL12-expressing iCAFs, such as a decrease in cytotoxic T cell and increase in myeloid suppressive proportions, creating the notorious immune suppressive TME well described in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Perturbation of Cxcl12 has also been associated extensively with B-cell lymphopoiesis 19 and various cancers, including pancreatic, breast, brain, thyroid, prostate, and skin. [20][21][22][23][24][25][26][27][28][29][30][31][32] Disruption of the CXCL12/CXCR4 axis promotes mobilization of hematopoietic stem and progenitor cells (HSPCs) from the BM to the blood, facilitating the process of cell collection for transplantation. 10,[33][34][35][36][37][38][39][40] Ding et al and Greenbaum et al have shown that cell type-specific deletion of CXCL12 in the BM results has selective effects on different types of HSPCs, suggesting that proximity to Cxcl12-expressing cells influences HSPC function.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB activity is known to play an important role in the expression of CXCR4 in human breast cancer cells, and the NF-κB-binding site is known to be found in the proximal region of the CXCR4 promoter [23,31]. Therefore, we evaluated the possible downregulation of CXCR4 by MIN via suppression of NF-κB.…”
Section: Discussionmentioning
confidence: 99%